Pressure Controlled Permeability in a Conduit Filled with Fractured Hydrothermal Breccia Reconstructed from Ballistics from Whakaari (White Island), New Zealand - Ben M. Kennedy; Aaron Farquhar; Robin Hilderman; Marlène C. Villeneuve; Michael J. Heap; Stan Mordensky; Geoffrey Kilgour; Art. Jolly; Bruce Christenson; Thierry Reuschlé (Geosciences, 2020)
Breccia-filled eruption conduits are dynamic systems where pressures frequently exceed critical thresholds, generating earthquakes and transmitting fluids. To assess the dynamics of breccia-filled conduits, we examine lava, ash tuff, and hydrothermal breccia ballistics with varying alteration, veining, fractures, and brecciation ejected during the 27 April 2016 phreatic eruption of Whakaari/White Island. We measure connected porosity, strength, and permeability with and without tensile fractures at a range of confining pressures. Many samples are progressively altered with anhydrite, alunite, and silica polymorphs. The measurements show a large range of connected porosity, permeability, and strength. In contrast, the cracked samples show a consistently high permeability. The cracked altered samples have a permeability more sensitive to confining pressure than the unaltered samples. The permeability of our altered ballistics is lower than surface rocks of equivalent porosity, illustrating that mineral precipitation locally blocked pores and cracks. We surmise that alteration within the conduit breccia allows cracks to form, open and close, in response to pore pressure and confining pressure, providing a mechanism for frequent and variable fluid advection pulses to the surface. This produces temporally and spatially variable geophysical and geochemical observations and has implications for volcano monitoring for any volcano system with significant hydrothermal activity.